2009
DOI: 10.1589/jpts.21.71
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Posture on Respiratory Function and Respiratory Muscle Strength in Normal Subjects

Abstract: Abstract.[Purpose] The purpose of this study was to compare the respiratory function and respiratory muscle strength in the different body positions in order to find the posture in which it is easiest to cough up secretions or endotracheal aspirate.[Subjects] Fifteen non-smoking healthy women participated. All subjects gave their written consent to the study. [Methods] We measured respiratory muscle strength and respiratory function in three postures: sitting, supine, and 45 degree rotative prone.[Results] Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 10 publications
0
21
0
4
Order By: Relevance
“…14---17 This finding may be related to the favorability of deep breaths in this posture, and overcomes the tendency to airway closure related to changes in lung compliance and lower pressure of the abdominal organs in relation to the diaphragm. 18 The upright position showed the highest increases in FVC. A similar finding was reported by other authors who suggest that the upright position provides greater mechanical advantage to the respiratory muscles, as abdominal contents do not interfere with diaphragm displacement and, thus, generates higher ventilation pressures.…”
Section: Discussionmentioning
confidence: 90%
“…14---17 This finding may be related to the favorability of deep breaths in this posture, and overcomes the tendency to airway closure related to changes in lung compliance and lower pressure of the abdominal organs in relation to the diaphragm. 18 The upright position showed the highest increases in FVC. A similar finding was reported by other authors who suggest that the upright position provides greater mechanical advantage to the respiratory muscles, as abdominal contents do not interfere with diaphragm displacement and, thus, generates higher ventilation pressures.…”
Section: Discussionmentioning
confidence: 90%
“…The different body positions have influenced on the lungs volume and muscle length-tension relationship. These factors have the effect on the mean expiratory pressure and peak expiratory flow [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In our review of previous studies of respiratory functions in relation to position, we found that studies have been conducted on normal subjects 9,10) , cerebral palsy patients 11) , and spinal cord injury patients 12,13) . However, objective data on changes in the chest mobility and pulmonary function of stroke patients in relation to changes in position are scarce.…”
Section: Introductionmentioning
confidence: 99%